Factors Affecting The Use Of Accounting Information With Environmental Uncertainty As A Moderating Variable - Diva Maulidah; Lia Ristiani; Alselina Saputri; Acep Komara (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
We realize that accounting information is very important for MSMEs today in the era of digitalization, where this research aims to obtain empirical evidence of variables that can influence it. The total research population was 50 MSMEs in the city of Cirebon and the sample was 40 MSMEs because of the population of 50 MSMEs that had used computerization, there were 40 MSMEs. The purposive sampling method was chosen to determine the sampling technique. The data analysis technique uses Moderated Analysis Regression (MRA). The conclusion that can be shown is as follows: the use of accounting information can be influenced by accounting knowledge or accounting training. The owner's education does not affect the use of accounting information. The use of accounting information can also be influenced by business size/scale of business. Environmental uncertainty can strengthen the influence of accounting knowledge on the use of accounting information. Environmental uncertainty cannot strengthen the effect of accounting training. The results of this research can be used as a reference for MSMEs to be motivated to use accounting information to improve MSME performance.